2011
DOI: 10.1093/chemse/bjq146
|View full text |Cite
|
Sign up to set email alerts
|

The K+-H+ Exchanger, Nigericin, Modulates Taste Cell pH and Chorda Tympani Taste Nerve Responses to Acidic Stimuli

Abstract: The relationship between acidic pH, taste cell pH(i), and chorda tympani (CT) nerve responses was investigated before and after incorporating the K(+)-H(+) exchanger, nigericin, in the apical membrane of taste cells. CT responses were recorded in anesthetized rats in vivo, and changes in pH(i) were monitored in polarized fungiform taste cells in vitro. Under control conditions, stimulating the tongue with 0.15 M potassium phosphate (KP) or 0.15 M sodium phosphate (NaP) buffers of pHs between 8.0 and 4.6, KP or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In the case of actinomycetes, antibiotics such as nigericins, oligomycins and actinomycins, among others, were identified. Nigericins are ionophores that catalyze the electroneutral exchange of K + for H + [ 29 ], whereas oligomycins and actinomycins act at the level of mitochondrial function and transcription, respectively [ 30 , 31 ]. Many of the known compounds identified are produced by species of the genus Streptomyces .…”
Section: Resultsmentioning
confidence: 99%
“…In the case of actinomycetes, antibiotics such as nigericins, oligomycins and actinomycins, among others, were identified. Nigericins are ionophores that catalyze the electroneutral exchange of K + for H + [ 29 ], whereas oligomycins and actinomycins act at the level of mitochondrial function and transcription, respectively [ 30 , 31 ]. Many of the known compounds identified are produced by species of the genus Streptomyces .…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 also lists the different solutions containing specific activators and blockers that were applied to the tongue topically to effect changes in fungiform taste cell pH i , [Ca 2+ ] i , cAMP, cGMP and protein kinase A (PKA). Direct measurement on isolated polarized fungiform taste bud cells showed that pH i changes can be altered by varying the apical solution pH (pH o ), such that, a given change in pH o corresponded to a unique change in pH i [20] . In previous studies, the maximum increase in the Bz-sensitive NaCl CT response was obtained by stimulating the tongue with 100 mM NaCl solutions at pH 10.3 relative to pH 7.0 [11] .…”
Section: Methodsmentioning
confidence: 99%
“…This is a standard approach to calibrate pH ex vivo. 44,45 The pH response experiment was performed at 37 °C for 1 h, and then the resultant cells were investigated by LSCM. Figure 3A−C shows the results for HeLa cells.…”
mentioning
confidence: 99%